2001
DOI: 10.1021/jp012733r
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Photoionization Processes in Fe(C5H5)2

Abstract: Density Functional calculations have been carried out to determine the photoionization cross section and the asymmetry parameter profiles of Fe(C 5 H 5 ) 2 , using an explicit treatment of the continuum wave function. An accurate numerical treatment is employed to ensure convergence of the calculated photoemission profiles without further potential approximation. All valence and carbon and metal core ionizations are investigated over a wide energy range. A very satisfactory agreement is obtained with the vast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Clark et al 8 studied the metalligand interaction in 3d sandwich complexes. Two typical sandwich clusters, Fe(C 5 H 5 ) 2 [18][19][20][21][22][23][24][25][26][27][28][29] and Cr(C 6 H 6 ) 2 , 23,24,27,[30][31][32][33][34][35][36][37][38][39][40][41][42] have been studied extensively. For Fe(C 5 H 5 ) 2 , the metal Fe atom contributes eight electrons (3d 6 4s 2 ) and each of the C atoms contributes one electron, which follows the 18-electron principle.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al 8 studied the metalligand interaction in 3d sandwich complexes. Two typical sandwich clusters, Fe(C 5 H 5 ) 2 [18][19][20][21][22][23][24][25][26][27][28][29] and Cr(C 6 H 6 ) 2 , 23,24,27,[30][31][32][33][34][35][36][37][38][39][40][41][42] have been studied extensively. For Fe(C 5 H 5 ) 2 , the metal Fe atom contributes eight electrons (3d 6 4s 2 ) and each of the C atoms contributes one electron, which follows the 18-electron principle.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among these, Fe(C 5 H 5 ) 2 (Refs. [4][5][6][7][8][9][10][11][12][13][14] and dibenzenechromium Cr(C 6 H 6 ) 2 (Refs. 10, 11, and 15-27) as two typical sandwich clusters have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…37 A series of small carborne molecules containing multiple aromatic B 3 and B 4 units have been reported by Berndt and co-workers. [38][39][40][41] Up to now, some theoretical confirmations have been reported to design potential sandwich-like complexes based on the pure boron units B 3 − , 31 34 and B [8][9][10][11][12][13][14] . 35 In particular, Zhai and co-workers 36 have demonstrated that B 12 can be viewed to be analogous to C 6 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies describing their electronic structure and the nature of metal-ligand bonding have been published. Some studies used theoretical methods to investigate photoionization and photoexcitation processes in the parent ferrocene [2,3]. Others used UV photoelectron spectroscopy (UPS) to probe the nature of metal-ligand bonding in ferrocenes [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%